Visual-Text Integration in Digital Public Service Announcement: A Strategy to Fight Fake News Spread - Retno Purwani Sari; Tatan Tawami (Aksara, 2023)
The purpose of the current study is to evaluate public service announcements (PSA’s): how visual and verbal rhetoric modes present an intended message. Differences in modes suggest different effects, and rhetoric promotes the power to persuade and convince others. As the growing interest in social media use, PSAs become a complex example of multimodal communication: combining verbal texts and visual images establish natural language in this world. The study looked at the question, how the combinations of texts and images work. Within this scope, Kress & van Leeuwen’s Visual Grammar theory and Halliday’s SFL theory were applied along with SF-MDA suggested by O’Halloran & Lim-Fei. The method of analytic descriptive qualitative allows the study to investigate and explain the issue elaborately. The results of this study show the combinations of all resources potentially motivate interactive participants to do the action after the investment of knowledge. Due to the increased importance of social movement, it is estimated that the findings potentially contribute to represent values intended by both public and private sectors. AbstrakTujuan dari penelitian ini adalah untuk mengevaluasi bagaimana retorika moda visual dan verbal menyampaikan pesan dalam pengumuman layanan umum. Perbedaan penggunaan moda menunjukkan dampak yang berbeda, sedangkan retorika memperlihatkan adanya kuasa untuk mempengaruhi dan meyakinkan orang lain. Dengan tingginya minat untuk menggunakan media sosial, PSA menjadi contoh komunikasi multimodal yang kompleks karena menggabungkan teks verbal dan gambar visual untuk menciptakan bahasa alami. Penelitian ini menjawab pertanyaan tentang bagaimana kombinasi teks dan gambar bekerja. Dalam cakupan ini, teori Tata Bahasa Visual oleh Kress & van Leeuwen dan teori SFL oleh Halliday diterapkan bersama dengan SF-MDA yang dicetuskan oleh O'Halloran & Lim-Fei. Metode deskriptif kualitatif analitis memungkinkan penelitian ini untuk menyelidiki dan menjelaskan masalah secara rinci. Hasil penelitian ini menunjukkan bahwa kombinasi semua sumber daya berpotensi memotivasi individu yang berinteraksi untuk melakukan tindakan yang disarankan setelah mereka memahami teorinya. Mengingat pentingnya aktivitas sosial, temuan ini diindikasikan berkontribusi dalam merepresentasikan nilai-nilai yang diinginkan oleh sektor publik maupun swasta.